Análise de confiabilidade no desenvolvimento de tratores agrícolas - Richter, Paulo Eduardo (2006)
The reliability of products has played a very important role for the competitiveness of enterprises. Foremost on the agricultural machinery area, where the reliability of the machinery will impact directly the production costs and profitability of farms. Agricultural tractors are complex machines with diverse systems and components interacting among themselves and establishing a dependency relationship among their performances. When these machines fail, are restored to recover their production capability. Many different techniques for reliability study have been developed based on components reliability studies, when testes under well defined conditions of bench tests to replicate well-known failure modes. Statistical distributions are used to represent the failures behavior of different kind of tests. Most of these studies, though, were developed for components that will be replaced when failed. Therefore they have to be analyzed under techniques that are suited for repairable systems. Many repairable systems have been analyzed with techniques that are only suited for non-repairable systems. This work proposes a comparison between the two techniques to analyze the differences and advantages of each one, and its applicability to the development of agricultural tractors